Chalcogen bonds: Hierarchical ab initio benchmark and density functional theory performance study - de Azevedo Santos, Lucas; Ramalho, Teodorico C; Hamlin, Trevor A; Bickelhaupt, F Matthias (Journal of computational chemistry, 2021)
We have performed a hierarchical ab initio benchmark and DFT performance study of D2 Ch•••A- chalcogen bonds (Ch = S, Se; D, A = F, Cl). The ab initio benchmark study is based on a series of ZORA-relativistic quantum chemical methods [HF, MP2, CCSD, CCSD(T)], and all-electron relativistically contracted variants of Karlsruhe basis sets (ZORA-def2-SVP, ZORA-def2-TZVPP, ZORA-def2-QZVPP) with and without diffuse functions. The highest-level ZORA-CCSD(T)/ma-ZORA-def2-QZVPP counterpoise-corrected complexation energies (ΔECPC ) are converged within 1.1-3.4 kcal mol-1 and 1.5-3.1 kcal mol-1 with respect to the method and basis set, respectively. Next, we used the ZORA-CCSD(T)/ma-ZORA-def2-QZVPP (ΔECPC ) as reference data for analyzing the performance of 13 different ZORA-relativistic DFT approaches in combination with the Slater-type QZ4P basis set. We find that the three-best performing functionals are M06-2X, B3LYP, and M06, with mean absolute errors (MAE) of 4.1, 4.2, and 4.3 kcal mol-1 , respectively. The MAE for BLYP-D3(BJ) and PBE amount to 8.5 and 9.3 kcal mol-1 , respectively.
Keywords: chalcogen bonds; benchmark study; density functional calculations; coupled-cluster; noncovalent interactions